The Advance of African Capital : The Growth of Nigerian Private Enterprise. - Forrest, Tom. (Edinburgh : Edinburgh University Press, 1994)
Combining ethnographic and historical perspectives, this study is the most detailed, most extensive account of medium- and large-scale African business. Not only a valuable digest of business activities, this important study also challenges existing views about African enterprise and is highly relevant to policy-makers concerned with economic development.
Description based upon print version of record.
JSTOR
Keywords: Business enterprises -- Nigeria -- History -- 20th century; Saving and investment -- Nigeria -- History -- 20th century; Free enterprise -- Nigeria -- History -- 20th century; Entrepreneurship -- Nigeria -- History -- 20th century; Entreprises -- Nigeria -- Histoire -- 20e siècle.; Entrepreneuriat -- Nigeria -- Histoire -- 20e siècle.; Business enterprises; Entrepreneurship; Free enterprise; Saving and investment; Nigeria; 1900-1999; History